THE EFFECT OF QUIZIZZ ON STUDENTS’ READING COMPREHENSION OF GRADE X AT SMK SWASTA PAB 1 HELVETIA ACADEMIC YEAR 2023-2024 - Ningsih, Nur Widya; Rahmawati, Wiki Tedi; Lubis, Sofia Idawati (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
This research aimed to find out whether the use of quizizz gave significant effect or not on students’ reading comprehension. The research was designed as a quasi-experimental with quantitative approach. The population of this research was the tenth-grade students of SMK SWASTA PAB 1 Helvetia. The sample was two parallel class namely X-Tbsm 1 which consisted of 30 students as the control class and X-Tbsm 2 which consisted of 30 students as the experimental class. Both classes were given pre-test and post-test. The experimental class was given treatment using Quizizz. Data analysis employed SPSS 29. Pre-test results for the experimental group were 62.67, whereas those for the control group were 60.00. while the experimental class's post-test score was 80.00 and the control classes was 70.33. Calculating the T-test revealed a significant difference. The analysis finding revealed that the sig (2-tailed) value was 0.01< 0.05, indicating that H0 was rejected and Ha was approved. As a result, it was possible to draw the conclusion that Quizizz gave a significant effect on students’ reading comprehension, particularly the descriptive text. Keywords: Quizizz, Reading Comprehension, Descriptive Text